FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS HIDUP PASIEN TB PARU DI RUMAH SAKIT KHUSUS PARU LUBUK ALUNG SUMATERA BARAT - Suriya, Melti (Jurnal Keperawatan Abdurrab, 2018)
Quality of life is a persons perception and expectations of living standards, poor quality of life is often experienced by chronic diseases, especially pulmonary TB. Special Hospital Pulmonary Hospital West Sumatra is the number of visits pulmonary tuberculosis patients most in 2016 is 1016 people. The aim of research to determine the factors associated with pulmonary TB Patient Quality of Life in Lung Special Hospital West Sumatra Lubuk Alung. This type of research is analytic with cross sectional design. The population in this study were all pulmonary TB patients who seek treatment at Special Hospital Pulmonary West Sumatra. Data research collection was performed on 21 June to 21 July 2017 data was collected using a questionnaire. The sampling technique is simple random block sampling with a sample of 96 peolpe. Data was analyzed by univariate and bivariate with Chi-Square test. The study found that more than half (63.5%) continued treatment, more than half (66.7%) did not receive the support of the family, more than half (57.3%) experienced depression, more than half (62.5% ) quality of life of poor TB patients. There is a long-standing relationship with the treatment of pulmonary tuberculosis patients life quality p value of 0.000 (p <0.05). There is a relationship of family support and quality of life of patients with pulmonary TB p value of 0.000 (p <0.05). There is a relationship of depression with quality of life of patients with pulmonary tuberculosis in the lungs Special Hospital West Sumatra Lubuk Alung  p value (p <0.05). Duration of treatment, family support and depression affect the quality of life of patients with TB. To improve the quality of life of TB patients need the support of family, treatment according to the rules and avoid depression in patients with TB so that TB patients will receive optimal health both physically and psychologically. It is expected that further research can continue this research with other factors that affect the quality of life of patients with TB.